2008
DOI: 10.3748/wjg.14.6564
|View full text |Cite
|
Sign up to set email alerts
|

Low level of galacto-oligosaccharide in infant formula stimulates growth of intestinal Bifidobacteria and Lactobacilli

Abstract: AIM:To investigate the effect of a new infant formula supplemented with a low level (0.24 g/100 mL) of galacto-oligosaccharide (GOS) on intestinal micro-flora (Bifidobacteria , Lactobacilli and E. coli ) and fermentation characteristics in term infants, compared with human milk and a standard infant formula without GOS. METHODS: Term infants (n = 371) were approached in this study in three hospitals of China. All infants started breast-feeding. Those who changed to formula-feeding within 4 wk after birth were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
125
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 24 publications
(35 reference statements)
14
125
1
5
Order By: Relevance
“…Infants fed formula supplemented with GOS (2.4 or 4.4 g/L) had lower fecal pH, as seen in BF infants, in comparison with infants fed non-supplemented formula. 91,93 Similar patterns were also observed when inulin, LOS, AOS, scGOS/lcFOS or scFOS/lcFOS/AOS was administrated to FF infants. 107,108,112,113 The effect of prebiotics on stool frequency and consistency has been evaluated in a systematic review.…”
Section: (Us)supporting
confidence: 52%
See 2 more Smart Citations
“…Infants fed formula supplemented with GOS (2.4 or 4.4 g/L) had lower fecal pH, as seen in BF infants, in comparison with infants fed non-supplemented formula. 91,93 Similar patterns were also observed when inulin, LOS, AOS, scGOS/lcFOS or scFOS/lcFOS/AOS was administrated to FF infants. 107,108,112,113 The effect of prebiotics on stool frequency and consistency has been evaluated in a systematic review.…”
Section: (Us)supporting
confidence: 52%
“…116,117 BF infants generally have lower fecal pH and softer and more frequent stools compared to FF infants 91,92,118 ; therefore, several clinical studies have evaluated the influence of prebiotics on stool characteristics of infants (Table 2). Infants fed formula supplemented with GOS (2.4 or 4.4 g/L) had lower fecal pH, as seen in BF infants, in comparison with infants fed non-supplemented formula.…”
Section: (Us)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (25,32), we reported a significant and remarkably specific enrichment of Bifidobacterium populations in human subjects during dietary supplementation with GOS (as demonstrated by 454 sequencing, genus-specific qRT-PCR, and quantitative culture), which is in agreement with data from other GOS feeding studies (33)(34)(35)(36)(37)(38). Cultural enumeration of fecal samples during the human trial allowed us to identify individuals in which bifidobacteria were enriched by GOS and from whom strains likely to utilize GOS in vivo could be selected.…”
Section: Resultssupporting
confidence: 80%
“…Host-microbe interaction occurs along mucosal surfaces in the intestine of host. By mutual interaction with host, gut microbiota play essential roles in providing vital functions to host, such as protection against epithelial cell injury (Rakoff et al, 2004), metabolic regulation (Stappenbeck et al, 2002), GI tract development (Stappenbeck et al, 2001), immunomodulation by development of innate and adaptive immune responses, and absorption of nutrients (Fredrik et al, 2005;Ben et al, 2008).…”
Section: Composition Of Gut Microbiota and Its Interactions With Hostmentioning
confidence: 99%